Fluxnet Archive Product from Hyltemossa - Michal Heliasz; Natascha Kljun; Tobias Biermann; Jutta Holst; Thomas Holst; Peter Kornacher; Maj-Lena Linderson; Meelis Molder; Janne Rinne (Integrated Carbon Observation System, 2025)
Archive Product for Ecosystem Measurements. Fluxes, Meteo and ancillary measurements processed with the International standard FLUXNET procedure (ONEFlux suite) with different time aggregations.
Heliasz, M., Kljun, N., Biermann, T., Holst, J., Holst, T., Kornacher, P., Linderson, M., Molder, M., Rinne, J. (2025). Fluxnet Archive Product from Hyltemossa, 2017-12-31–2024-12-31, FLUXNET, https://hdl.handle.net/11676/8hMY0lY7kERIfokXkEpev-03
Keywords: Ecosystem Thematic Centre; carbon flux; meteo; none-ICOS; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap